Drug Clues for the Treatment of Fungal Catheter-Related Bloodstream Infection With Antifungal Lock Therapy - Li X; Yu B; Li H; Liu Z; Fu X; Jiao P; Wang L (Drug Design, Development and Therapy)
Xiuyun Li,1 Bing Yu,2 Hui Li,3 Zhirui Liu,4 Xiaohan Fu,1 Ping Jiao,5 Lei Wang6 1Infection and Microbiology Research Laboratory for Women and Children, Shandong Provincial Maternal and Child Health Care Hospital Affiliated to Qingdao University, Jinan, 250014, People’s Republic of China; 2Medical Affairs Department, Shandong Provincial Maternal and Child Health Care Hospital Affiliated to Qingdao University, Jinan, 250014, People’s Republic of China; 3Pediatric Department, Shandong Provincial Maternal and Child Health Care Hospital Affiliated to Qingdao University, Jinan, 250014, People’s Republic of China; 4Faculty of Medicine and Health, The University of Sydney, Camperdown NSW, 2050, Australia; 5Department of Pharmacy, Jinan Maternity and Child Care Hospital Affiliated to Shandong First Medical University, Jinan, 250012, People’s Republic of China; 6School of Pharmaceutical Science @ Institute of Materia Medica. Shandong First Medical University @ Shandong Academy of Medical Sciences, Jinan, 250117, People’s Republic of ChinaCorrespondence: Ping Jiao; Lei Wang, Email jiaopingonlyone@163.com; wanglei1118@sdfmu.edu.cnBackground: Biofilm formation often represents significant challenges in managing of bloodstream infections associated with catheter use.Objective: Antimicrobial lock therapy serves as an adjunctive treatment for catheter-related infections, effectively eradicating or inhibiting biofilm growth.Methods: This review synthesizes the current knowledge on antifungal lock therapy (ALT) targeting clinically common fungi, primarily Candida species, based on both in vitro and in vivo studies (animals and patients) from the past decade.Results: Amphotericin B (AmB) and echinocandins are identified as the most promising antifungal agents for ALT. Combinations of antifungal agents with other compounds, such as farnesol, Neosartorya fischeri antifungal protein 2, 8-hydroxyquinoline-5-(N-4-chlorophenyl) sulfonamide, and polyurethane, have also shown efficacy in ALT. Additionally, ethanol, doxycycline, tigecycline, and minocycline lock solutions can be effective in treating fungal infections.Conclusion: More comprehensive investigations and additional rigorous clinical trials are essential to thoroughly understand the safety and efficacy of ALT. This will facilitate the development of novel treatments for catheter-related fungal infections, thereby improving clinical outcomes.Keywords: antifungal lock therapy, catheter-related bloodstream infections, Candida